2004
DOI: 10.1111/j.1365-2141.2004.04972.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the use of fresh‐frozen plasma, cryoprecipitate and cryosupernatant

Abstract: The indications for transfusing fresh‐frozen plasma (FFP), cryoprecipitate and cryosupernatant plasma are very limited. When transfused they can have unpredictable adverse effects. The risks of transmitting infection are similar to those of other blood components unless a pathogen‐reduced plasma (PRP) is used. Of particular concern are allergic reactions and anaphylaxis, transfusion‐related acute lung injury, and haemolysis from transfused antibodies to blood group antigens, especially A and B. FFP is not indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
290
0
12

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 739 publications
(309 citation statements)
references
References 78 publications
7
290
0
12
Order By: Relevance
“…) [17] is around half that of the median (IQR) concentration of 5 g.l À1 (4.4-5.8) seen in the third trimester of pregnancy [26]. Administration of FFP to a pregnant patient at term may thus result in a reduction in fibrinogen levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…) [17] is around half that of the median (IQR) concentration of 5 g.l À1 (4.4-5.8) seen in the third trimester of pregnancy [26]. Administration of FFP to a pregnant patient at term may thus result in a reduction in fibrinogen levels.…”
mentioning
confidence: 99%
“…A pooled bag of cryoprecipitate from five donors contains 1.552 g in a mean volume of 189 ml [16]. The fibrinogen content of FFP is more variable; a typical unit contains 0.8 g in a volume of 300 ml [17].…”
mentioning
confidence: 99%
“…41 PCCs are widely used in the European community and have previously been cited as the agent of choice for urgent warfarin reversal. 42,47,48 A recent study comparing PCCs with FFP and vitamin K has demonstrated that PCCs may be superior to FFP and vitamin K by reducing the risk of hematoma growth. 49 Recombinant Factor VIIa Recombinant factor VIIa is a preparation of activated coagulation factor VII (factor VIIa) that is produced by recombinant DNA technology.…”
Section: Fresh Frozen Plasma (Ffp)mentioning
confidence: 99%
“…In the 2004 British Committee for Standards in Haematology (BCSH) guidelines [35], a target of 1 g.l À1 was suggested; in recognition of the changes in major bleeding management. A new guideline is due to be published, and this is likely to set a trigger for giving fibrinogen (in the form of cryoprecipitate) at 1.5-2.0 g.l À1 .…”
Section: Fibrinogenmentioning
confidence: 99%